Digital technology for health shows disparities in cancer prevention between digital health technology users and the general population in Romania - Pana, Bogdan C.; Ciufu, Nicolae; Ciufu, Carmen; Furtunescu, Florentina L.; Turcu-Stiolica, Adina; Mazilu, Laura (Frontiers in Oncology, 2023)
Introduction: Digital health services and technology are rapidly developing following the COVID-19 pandemic. This study’s aim was to reveal differences between users of digital health technology (DHT) and the general population with regard to cancer prevention. Materials and Methods: This was an observational study on a conventional sample of 270 DHT users with completed data, performed in September 2021. Results: There was a significant difference in the proportion of users reporting the screening tests results between DHT users and the general population, which was 2-6 times higher in the DHT group. Digital technologies applied to the "self-care" model were more suitable for individuals among internet-literate populations. Discussion: The inclusion of digital technologies in a self-care model may be more suitable for individuals who are internet-literate; thus, in a preventative health organisational framework DHT should be integrated and used at the primary care level in the general population, to improve health disparities in the preventative health domain.